THE ROLE OF THE CONSTRUCTION INDUSTRY IN ECONOMIC GROWTH AND SUSTAINABLE DEVELOPMENT - CUCOS, Stela; TURCAN, Rina (Journal of Social Sciences)
The construction industry is one of the determining driver of economic growth and sustainable development, particularly in developing economies, where it contributes significantly to GDP and employment creation. This study investigates the dual role of the sector as an economic engine and a sustainability agent, focusing on Moldova and the European Union. The research hypothesizes that integrating innovative technologies and circular economy principles can enhance the sector’s economic and environmental performance while addressing regional disparities. The study aims to analyse the sector's contributions to GDP, employment, and sustainability, identifying challenges and opportunities for improvement. Using a quantitative framework, the research assesses the contributions of construction activities to GDP formation in dynamics, including by country, sector-specific sustainable practices and activity structure. In this article such tools as linear regression, comparative analysis and cause-effect analysis are used in order to achieve the research aim. The findings reveal significant regional disparities, with stable growth in developed economies and higher volatility in developing countries, highlighting the impact of the construction sector on economic development. The findings emphasize the importance of specific policies geared towards increasing skills, keeping the workforce at home and mainstreaming sustainable practices. This research provides a clear vision of the construction industry's role in stimulating economic growth and promoting sustainable development through innovation and specific sustainable practices.